Efektivitas Pemberian Jus Strawberry dan Madu Terhadap Peningkatan Hemoglobin Pada Ibu Hamil Trimester III di Puskesmas Ketapang Kabupaten Lampung Utara - Cenayang Dara Yasa; Lili Anggraini (Malahayati Nursing Journal, 2024)
ABSTRACT Anemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. Iron deficiency anemia in the mother can affect the growth and development of the fetus/infant during and after pregnancy. Based on the 2018 Riskesdas data in Indonesia, 48.9% of pregnant women experience anemia. The coverage of anemia in pregnancy in Lampung Province in 2021 is 43.5%. This study aims to determine the effectiveness of giving strawberry juice and honey to increasing hemoglobin in third trimester pregnant women at the Ketapang Health Center, North Lampung Regency in 2023. Type of quantitative research and pre-experimental design with Non-Equivalent Control Group. The population of all third trimester pregnant women is 15 responden. Sampling using purposive sampling technique, statistical tests used paired t test (paired t test). The results of the study showed that the average increase in hemoglobin levels before being given strawberry juice and honey in third trimester pregnant women with anemia had an average value of 10.513 gr/dl. The average increase in hemoglobin levels after being given strawberry juice and honey in third trimester pregnant women with anemia has an average hemoglobin level of 11.287gr/dl. There is an effect of giving strawberry juice and honey on hemoglobin levels in third trimester pregnant women with anemia, with a p value = 0.000. It is recommended that pregnant women pay attention to nutrition during pregnancy and routinely do pregnancy exercise and are advised to consume strawberry juice and honey as a companion in consuming Fe tablets and are good for daily consumption. Keywords: Strawberry Juice And Honey, Hemoglobin Levels, Trisemester III  ABSTRAK Anemia pada ibu hamil dapat meningkatkan risiko kelahiran prematur, kematian ibu dan anak, serta penyakit infeksi. Anemia defisiensi besi pada ibu dapat mempengaruhi pertumbuhan dan perkembangan janin/bayi saat kehamilan maupun setelahnya. Berdasarkan data Riskesdas 2018 di Indonesia sebesar 48,9% ibu hamil mengalami anemia. Cakupan anemia pada kehamilan di Provinsi Lampung pada tahun 2021 sebesar 43,5%. Penelitian ini bertujuan mengetahui efektivitas pemberian jus strawberry dan madu terhadap peningkatan hemoglobin pada ibu hamil trimester III di Puskesmas Ketapang Kabupaten Lampung Utara Tahun 2023. Jenis penelitian kuantitatif dan rancangan pra eksperiment dengan Non-Equivalent Control Group. Populasi seluruh ibu hamil trimester III sebanyak 15 orang. Pengambilan sampel menggunakan teknik purposive sampling, uji statistik yang digunakan uji t berpasangan (paired t test). Hasil penelitian rata–rata peningkatan kadar hemoglobin sebelum diberikan jus strawberry dan madu pada ibu hamil trimester III dengan anemia mempunyai nilai rata-rata 10,513 gr/dl. Rata–rata peningkatan kadar hemoglobin sesudah diberikan jus strawberry dan madu pada ibu hamil trimester III dengan anemia mempunyai nilai rata-rata kadar hemoglobin 11,287gr/dl. Ada pengaruh pemberian jus strawberry dan madu terhadap kadar hemoglobin pada ibu hamil trimester III dengan anemia, dengan p-value = 0,000. Disarankan ibu hamil agar memperhatikan gizi selama kehamilan serta rutin melakukan pemeriksaan kehamilan dan disarankan untuk mengkonsumsi jus strawberry dan madu sebagai pendamping dalam mengkonsumsi tablet Fe dan baik untuk dikonsumsi setiap hari. Kata Kunci: Jus Strawberry Dan Madu, Kadar Hemoglobin, Trismester III